Joint Property Division in Indonesia: A Gender Equality Viewpoint - Rouf, Abd; Ch, Mufidah; Mahmudi, Zaenul (De Jure: Jurnal Hukum dan Syari'ah, 2023)
The distribution of joint property regulated under the Compilation of Islamic Law is considered very effective due to the legal certainty guaranteeing that ex-husbands and wives receive a half share. However, these provisions cannot be fully applied to estranged husbands and wives because family background conditions vary. There are certain conditions where husbands and wives have multiple roles, and this occurrence needs to be more profoundly studied. Therefore, this study is presented to analyze the distribution of joint assets according to the roles assigned in the household. This research employed a normative-legal method and statutory and conceptual approaches. The primary data in this study is the Compilation of Islamic Law (KHI). The researcher analyzed activity profiles, access and control between husband and wife as specified in KHI norms by using a gender equity analysis tool. The results show that the fair value of the distribution of joint assets which refers to the division of roles between husband and wife contained in the KHI has set different roles between the two, in which the husband works outside the house while the wife serves as a housewife. Meanwhile, currently, all roles performed by husbands can also be performed by wives and the other way around, while unchangeable roles remain in the biological or reproductive role. So the division of roles cannot be interpreted literally because the husband or wife has flexible and fair access and control. Keywords: joint property; gender equality; spouses rights.